Major Barbara - Shaw, Bernard, 1856-1950 (Salt Lake City, UT : Project Gutenberg, 2003)
"Major Barbara" by Bernard Shaw is a three-act play written and premiered in 1905. The story follows Barbara Undershaft, an idealistic Salvation Army officer, whose work helping London's poor is challenged when her estranged father reappears as a wealthy munitions manufacturer. When he donates his "tainted" money to the Salvation Army, Barbara faces a moral crisis. Her father argues that providing steady employment does more good than charity work, forcing Barbara to confront difficult questions about poverty, wealth, and how to truly help society. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Major_Barbara
Release date is 2003-02-01
Produced by Eve Sobol. HTML version by Al Haines.
Keywords: Fathers and daughters -- Drama; Salvation Army -- Drama; Children of the rich -- Drama; Crime -- Drama; Didactic drama